1993
DOI: 10.1002/ajmg.1320450410
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism for deletion 17p11.2 in a boy with the Smith‐Magenis syndrome

Abstract: We describe a 14-year-old boy with physical and behavioral manifestations of the Smith-Magenis syndrome. Low level mosaicism (11%) for deletion 17p11.2 was found in peripheral blood lymphocytes. The deletion was also observed in 100% of metaphases examined from skin fibroblast cultures. We confirm that the Smith-Magenis syndrome is associated with a highly recognizable phenotype. Because evidence of the abnormal cell line may be minimal or absent in peripheral blood, fibroblast studies are indicated for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…2). As indicated in Table 1 (Finucane et al, 1993;Juyal et al, 1995). This patient was originally reported as mosaic for del( 17)p 11.2 by routine G-banding analysis, but FISH analysis revealed a dele tion in all cells.…”
Section: Phenotypic Analysis O F Patients With Del( 17)(pi 12)mentioning
confidence: 85%
See 1 more Smart Citation
“…2). As indicated in Table 1 (Finucane et al, 1993;Juyal et al, 1995). This patient was originally reported as mosaic for del( 17)p 11.2 by routine G-banding analysis, but FISH analysis revealed a dele tion in all cells.…”
Section: Phenotypic Analysis O F Patients With Del( 17)(pi 12)mentioning
confidence: 85%
“…diagnosis of mosaicism in a true deletion case (Finucane et al, 1993;Juyal et al, 1995;Juyal et al, 1995; and therefore, result in incorrect diagnoses. While the common SMS deletion is estimated to be 4-5 Mb.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of mosaic deletion 17p11.2 patients is presented in Table I. Based on karyotype analysis, mosaicism was initially thought to be the case in three reports [Finucane et al, 1993;Juyal et al, 1995;Hou, 2003], but further studies revealed that the deletion was present in 100% of cells.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 23 such cases have been reported. They include mosaicism for duplications [Harrod et al, 1980;Cantu and Ruiz, 1986;Serotkin et al, 1988;Blouin et al, 1991;Jewell et al, 1992;Dixon et al, 1993;Gardner et al, 1994], deletions [Wilson and Lin, 1988;Ritter et al, 1990;Patel et al, 1992;D'Alessandro et al, 1992;Finucane et al, 1993;Gordon et al, 1993;Sybert, 1994], insertions [Nielsen et al, 1978], isochromosomes [Robinow et al, 1989;Stanley et al, 1993;Sybert, 1994], and derivative chromosomes [Tsien et al, 1991;Powell et al, 1991;Pelligrino et al, 1995].…”
Section: Discussionmentioning
confidence: 99%